Lyα Imaging around the Hyperluminous Dust-obscured Quasar W2246–0526 at z = 4.6 - Luo, Yibin; Fan, Lulu; Liang, Yongming; Hu, Weida; Wang, Junxian; Zheng, Zhen-ya; Lin, Zheyu; Tao, Bojun; Lin, Zesen; Cai, Minxuan; Huang, Mengqiu; Wan, Zhen; et al. (The Astrophysical journal, 2024)
Hot dust-obscured galaxies (hot DOGs) are a population of hyperluminous, heavily obscured quasars discovered by the Wide-field Infrared Survey Explorer all-sky survey at high redshift. Observations suggested the growth of these galaxies may be driven by mergers. Previous environmental studies have statistically shown hot DOGs may reside in dense regions. Here we use the Very Large Telescope narrowband and broadband imaging to search for Ly α emitters (LAEs) in the 6. ′ 8 × 6. ′ 8 field of the hot DOG W2246−0526 at z = 4.6. W2246−0526 is the most distant hot DOG. We find that there is an overdensity of LAEs in the W2246−0526 field compared with the blank fields. This is direct evidence that this most distant hot DOG is in an overdense environment on the Mpc scale, and the result relates to the merger origin of hot DOGs.